2021
DOI: 10.1101/2021.12.12.472253
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Scanning the RBD-ACE2 molecular interactions in Omicron variant

Abstract: The emergence of new SARS-CoV-2 variants poses a threat to the human population where it is difficult to assess the severity of a particular variant of the virus. Spike protein and specifically its receptor binding domain (RBD) which makes direct interaction with the ACE2 receptor of the human has shown prominent amino acid substitutions in most of the Variants of Concern. Here, by using all-atom molecular dynamics simulations we compare the interaction of Wild-type RBD/ACE2 receptor complex with that of the l… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 20 publications
3
13
0
Order By: Relevance
“…The preprint of this study was the first in the literature to show via all-atom MD simulations the effect of the omicron BA.1 mutations on RBD-PD interactions and binding strength. Our findings have been supported with recent computational 17,18 and experimental studies 11,19-21 . There is currently no consensus regarding the exact binding energy of the BA.1 omicron variant S protein to ACE2.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The preprint of this study was the first in the literature to show via all-atom MD simulations the effect of the omicron BA.1 mutations on RBD-PD interactions and binding strength. Our findings have been supported with recent computational 17,18 and experimental studies 11,19-21 . There is currently no consensus regarding the exact binding energy of the BA.1 omicron variant S protein to ACE2.…”
Section: Discussionsupporting
confidence: 90%
“…Binding free energies ranging from −107.04 to −635.32 kcal/mol were reported by post-processing all-atom MD trajectories. 17,18 Furthermore, K D values ranging 25.3-38.9 nM were reported for the BA.1 omicron variant. 11,1921 While these approaches report different K D values, consistent with our findings, they all estimate a higher binding strengths for RBD BA.1 compared to the RBD WT .…”
Section: Discussionmentioning
confidence: 96%
“…Our results add to the evidence (Iketani et al, 2022;Liu et al, 2022) that single amino acid changes may confer full resistance to neutralizing antibodies. In comparison, mutation of E484A that has also been observed in other SARS-CoV-2 VOCs and was suggested to be associated with immune-escape (Rath et al, 2022) had only marginal effects on neutralization sensitivity.…”
Section: Discussionmentioning
confidence: 81%
“…There are several experimental and computational studies which clearly show the cause of a high transmission of the Omicron variant and its immune evasion [22][23][24][25] . The increase in the binding of the SARS-CoV-2 receptor ACE2 with the RBD is the main cause of the enhanced transmission of the Omicron variant.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, it was shown that the mutations in the Omicron RBD yields more contacts, hydrogen bonds and buried surface area at the interface of spike RBD and ACE-2 receptor, as compared to the original strain 24 . Rath et al 22 reported 2.5 times stronger binding between the mutated residues and ACE-2 receptor together with a much relaxed dynamics of the complex, as compared to the wild type.…”
Section: Introductionmentioning
confidence: 99%